DESCRIPTIVE EPIDEMIOLOGY OF HEMOPHILIA AND OTHER COAGULATION DISORDERS IN MANSOURA , EGYPT - Youssef Al Tonbary; Rasha ElAshry; Maysaa El Sayed Zaki (Mediterranean Journal of Hematology and Infectious Diseases)
Hemophilia represent the most severe inherited bleeding  disorder (INB) , it’s thought to affect inviduals from all geographical areas in equal frequency. In Egypt which has a population of approximately (80million) consanguineous marriage are frequent, therefore autosomal recessive coagulation disorders reach a higher prevalence than in many other countries. The primary aim of this study was to describe the epidemiological situation of hemophilia in Mansoura, Egypt ,as based on retrospective analysis of clinical records Mansoura University Children Hospital between years 2000 and 2008. The second aim was to assess the orthopedic complications and occurrence of hepatitis C in those patients and relate this status to the type of replacement therapy received prior to the study. The study included 72 children with hematological disorders registered from 2000 to 2008 in MUCH. The hemophilic patient was defined as a person with physician-diagnosed hemophilia A or B and a measured factor VIII or IX activity level of 30% or less. Persons with acquired inhibitors of FVIII or FIX excluded. Severity level was categorized as mild if the factor activity level was 6–30%, moderate if 1–5% and severe if